Analisis Penilaian Kinerja Karyawan Menggunakan Metode WASPAS - Sunardi Sunardi; Rusydi Umar; Dewi Sahara Nasution (STMIK Budi Darma, 2022)
An employee is an asset to the company. The success of the company in achieving its goals depends largely on the ability of human (employee) resources to perform the task assigned to him. The Indonesian government is optimistic the rupiah will continue to strengthen to rp9,100 per dollar, he said. Employee performance assessment analysis is using a systemated aggregated sum product assessment (waspas). The waspas method is used because it can reduce errors or optimize for the highest and lowest valuation with the excellence of looking for the best option option using a unique combination of two Wells known as MCD mexcellence, the WMM and the heavy-product model (WPM). The research stages conducted are problem identification, literature studies, data collection, value-weight determination, results analysis, employee determination, and finally drawing a conclusion. The study is conducted using a descriptive qualitative approach, one that employs qualitative and descriptive data. The type of qualitative descriptive research is often used to analyze events, phenomena, or circumstances socially. The study was conducted compulsively, a sample retrieval technique relying on its own judgment when selecting population members to participate in the study so that the study obtained five samples from the quality control division (qc) from a population of 150. Data collection through interviews and observations obtained data related to employees such as employee names, performance performance, divisions existing in kerry express, and criteria used in the assessment of lateness, error system, daily report, outstanding revenue, volume. Data analysis results in a reduction of data that gets meaningful information and facilitates the withdrawal of conclusions, presents data in the form of happy calculations, and concludes that the waspas method can be applied to the employee performance assessment system and can be used as the determining of the best workers. Weight of each criteria: lateness (25%), system improve (25%), daily report (25%), outstanding revenue (15%), and volume (10%). Results obtained from the 5 samples used that had a top yield value of 1.8208 for alternatives 1 (a1) and could be used for best employee decision-making.